The roles of KRAS in cancer metabolism, tumor microenvironment and clinical therapy - Qinglong Ma; Wenyang Zhang; Kongming Wu; Lei Shi (Molecular Cancer)
Abstract KRAS is one of the most mutated genes, driving alternations in metabolic pathways that include enhanced nutrient uptaking, increased glycolysis, elevated glutaminolysis, and heightened synthesis of fatty acids and nucleotides. However, the beyond mechanisms of KRAS-modulated cancer metabolisms remain incompletely understood. In this review, we aim to summarize current knowledge on KRAS-related metabolic alterations in cancer cells and explore the prevalence and significance of KRAS mutation in shaping the tumor microenvironment and influencing epigenetic modification via various molecular activities. Given that cancer cells rely on these metabolic changes to sustain cell growth and survival, targeting these processes may represent a promising therapeutic strategy for KRAS-driven cancers.